1, 3, 5-Triazine-Based Liquid Crystals: An Up-to-Date Appraisal of Their Synthetic Design and Mesogenic Properties. Issue 5 (2nd September 2020) - Bhagavath, Poornima; Shetty, Rajatha; Sunil, Dhanya
Abstract: Nature constructs captivating stable structures and assemblies using the principles of order and flexibility. A lot of literature evidence focuses on the design of mesogenic soft materials with a 1, 3, 5-triazine core due to its appealing structure and properties. Progress in the field of triazine-based liquid crystal molecules with emphasis on their synthesis and mesomorphic features is presented in this review. The prospects that could orient researchers to stimulate further efforts in this area are also presented.